The History and Future of Professional Development Schools in Kansas - Debbie K. Mercer; Scott Myers (Educational Considerations, 2014)
Quality clinical experiences are an integral component of effective teacher preparation programs. Evidence clearly indicates that experiences in classrooms, under the mentorship of effective teachers and mentors, greatly enhance the preservice teacher’s growth and development.
Keywords: Professional Development School (PDS); PreK-12 students; Kansas; Standards; recommendations; teaching; learning; community.